Wedge-Shaped Resection of the Posterior Bony Arch During Open Door Laminoplasty to Prevent Postoperative Motion Limitation. Issue 3 (February 2017) - Suh, Bo-Gun; Ahn, Myun-Whan; Kim, Ho-Joong; Yeom, Jin S.; Lee, Gun Woo
Abstract : Study Design: Prospective randomized double-arm noninferiority study. Objective: To evaluate an additional surgical procedure (wedge-shaped resection of the cranial portion of the posterior bony arch) during open-door laminoplasty (ODLP), and to compare the outcomes with those of conventional ODLP surgery. Summary of Background Data: In clinical practice, spine surgeons sometimes encounter patients who show bony impingement on lateral radiographs after ODLP; bony impingement may lead to reduced motion of the cervical spine and posterior neck pain. However, this problem has not been well studied, and no methods have been developed to prevent it. Methods: Of total 79 patients, 75 were enrolled and randomly assigned to either group A (additional procedure in ODLP, n = 38) or group B (ODLP alone, n = 37). The primary outcome measure was range of motion (ROM) of the cervical spine. Secondary endpoints included clinical outcomes based on pain intensity, 12-item short form health survey (SF-12), and modified Japanese Orthopedic Association scale; presence of bony impingement on dynamic lateral radiographs; surgical outcomes; and surgery-related complications. Results: ROM of the cervical spine was significantly greater at 6 months ( P = 0.04) and 1 year ( P = 0.02) postoperative in group A than in group B. Pain intensity at the posterior neck was significantly lower 1 year after surgery in group A than in group B ( P = 0.03). In lateral radiographs 1 year after surgery, the presence of posterior bony impingement was 0% in group A and 32.4% in group B ( P <0.01). Clinical outcomes and surgery-related complications were similar between groups. Conclusion: Performing wedge-shaped resection of the cranial portion of the posterior bony arch in ODLP surgery can lead to better outcomes than ODLP alone in terms of preservation of cervical ROM, prevention of posterior bony impingement, and amelioration of posterior neck pain. Level of Evidence: 2